2002
DOI: 10.1063/1.1480269
|View full text |Cite
|
Sign up to set email alerts
|

Parallel inhomogeneous flows in a thermally anisotropic plasma: The electrostatic ion-acoustic branch

Abstract: The linearized dispersion relation describing waves in a plasma having a uniform magnetic field, uniform density, and inhomogeneous parallel (to the magnetic field) flow is generalized to include thermal anisotropy (Ti⊥/Ti∥), a key feature existing in many space and laboratory plasmas. The growth rate and the real frequency at which the maximum growth rate occurs for the ion acoustic mode increases with increasing Ti⊥/Ti∥. The propagation angle, with respect to the background magnetic field, for ion acoustic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 32 publications
5
34
0
Order By: Relevance
“…Note that the previous dispersion relation is equivalent to the one presented by Spangler et al (2002). For the IA branch, b i 1 and, therefore, the n = 0 term dominates the series.…”
Section: Kinetic Theorymentioning
confidence: 84%
See 2 more Smart Citations
“…Note that the previous dispersion relation is equivalent to the one presented by Spangler et al (2002). For the IA branch, b i 1 and, therefore, the n = 0 term dominates the series.…”
Section: Kinetic Theorymentioning
confidence: 84%
“…For the IA branch, b i 1 and, therefore, the n = 0 term dominates the series. In their analysis, Scime et al (2003), Spangler et al (2002) and Spangler (2001) reported that the k 2 λ Di⊥ term has a negligible effect on the dispersion relation solutions. We follow the same procedure and consider wavelengths much larger than the Debye radius in order to guarantee quasi-neutrality.…”
Section: Kinetic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, according to the simulation results here and ignoring non-Maxwellian features of the particle distributions, the transient gradient in the relative magnetic field aligned drift as driven by the EIC wave has a negligible effect on the amplitude of IA oscillations. Additionally, the role of ion temperature anisotropy in the growth of shear-modified IA waves is to change the propagation direction or k z /k y , which is a critical term of Ganguli's generalized dispersion relation (Spangler et al, 2002;Teodorescu et al, 2003). As explained above, for a wide range of k z /k y values, the shear effect as part of EIC wave oscillations will be insignificant, and therefore ion temperature anisotropy needs to be addressed independently from the shear effect.…”
Section: Discussionmentioning
confidence: 99%
“…For the strong shear limit, no field aligned current was required at all to destabilize ion-acoustic modes. This work was then extended by Scime et al (2002) to include thermal anisotropy and by Spangler et al (2002) who considered the effect of ion and electron temperature anisotropies. None of these extensions of the original study, however, included collisions, which raises the issue of their applicability to ionospheric situations.…”
Section: Introductionmentioning
confidence: 99%